Pelayanan Publik di Kota Mataram: Program Public Safety Center (PSC) 119 Mataram Emergency Medical Service (MEMS) - Rahmad Hidayat; Ima Ferbiyanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
One of the well-known innovations in health services is the Public Safety Center (PSC) 119 program. An initiative program from the Ministry of Health and in collaboration with various local governments. In the city of Mataram, this service program is coupled with the Mataram Emergency Medical Service (MEMS), which only started in 2019. Researchers were trying to find out how implemented this program so that it can provide complete picture. This research is descriptive qualitative by collecting data through in-depth interviews, observation and documentation related to the PSC 119 MEMS program at Mataram City Hospital. Data analysis techniques use interactive data analysis techniques through data reduction, data presentation and drawing conclusions. As well as the process of testing the validity of the data with triangulation techniques. The results of the study show that this program has been implemented properly, where the home care program is most needed by the people of the city of Mataram. There are still obstacles in this program such as the lack of ambulance facilities with complete facilities and telecommunications networks.